Development and Contextualization of the Meaning of Sabîlillâh: A Study of Reality and Conditions in Indonesia - Nur Sillaturohmah Handayani; M Muthoifin (Demak Universal Journal of Islam and Sharia, 2024)
The purpose of this study is to understand and analyze the development and contextualization of the meaning of sabîlillâh: a study of reality and conditions in Indonesia. This research is included in the category of qualitative research that adopts a descriptive analysis approach and content analysis with a Philological / Semantic and Phenomenological approach. Data is obtained from various primary sources such as books, books, journals, and others and supporting secondary data sources. In this method, researchers attempt to illustrate existing phenomena by analyzing and presenting data or facts systematically, thus facilitating the understanding and process of concluding. The results showed that MUI tried to expand the meaning of ashnâf fî sabîlillâh through various zakat fatwas to answer the challenges and problems of the ummah today. MUI provides wider space in using zakat funds for public benefit and various benefits, such as legal case defence, scholarship assistance, amil zakat salaries, zakat foundation or institution operations, disaster management, clean water supply, and response to the COVID-19 pandemic and natural disasters. MUI's efforts in expanding the meaning of ashnâf fî sabîlillâh are by the concept of maqâshid as-syarî'ah, especially in safeguarding religion, life, reason, offspring, and property, both dharûriyyât, hâjiyyât, and tahsîniyyât. This is a relevant step in facing the growing social and economic challenges in society.